Empowering Students to Assess the State of Diversity, Equity, and Inclusion on Campus - Jonathan Auerbach; Christi Wilcox (Journal of Statistics and Data Science Education)
Universities and colleges have reevaluated their commitment to diversity, equity, and inclusion (DEI) over the past decade. Many have established DEI offices tasked with identifying and addressing barriers that limit the participation of students, faculty, and staff. The effects of these barriers are often reflected in the volumes of data on enrollment, graduation, and other facets of university life reported to the U.S. Department of Education each year. But it is unrealistic to expect even a generously resourced office to monitor the vast amount of data available. In this paper, we propose that instructors of project-based statistics and data science courses work with DEI offices (or offices with similar responsibilities) to have students use this data to investigate the state of DEI on campus. We describe a class project in which undergraduate students conducted their own independent assessments and submitted a short report summarizing their findings. The lesson proved rewarding to both the students and the DEI office: Students reported a variety of new and interesting trends. Students also gained a different perspective of campus diversity and a deeper appreciation for how diversity is calculated in practice. We conclude that students are an untapped resource that can help improve campus life as they develop their statistics and data science skills.